2018
DOI: 10.1002/jcb.27832
|View full text |Cite
|
Sign up to set email alerts
|

miR‐17‐5p promotes proliferation and epithelial‐mesenchymal transition in human osteosarcoma cells by targeting SRC kinase signaling inhibitor 1

Abstract: MicroRNA‐17‐5p (miR‐17‐5p) and epithelial‐mesenchymal transition (EMT) have been reported to participate in the development and progression of multiple cancers. However, the relationship between the miR‐17‐5p and EMT in osteosarcoma (OS) is still poorly understood. This study was to investigate the effects of the miR‐17‐5p and its potential mechanism in regulating proliferation, apoptosis, and EMT of human OS. Quantitative real‐time PCR was used to detect the miR‐17‐5p and SRC kinase signaling inhibitor 1 (SRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…To further elucidate the ceRNA network, considering that functional miRNA is known to regulate its target gene expression, the potential target of miR-17-5p was explored by bioinformatics analysis. Previous studies have revealed transforming growth factor-β receptor 2, SRC kinase signaling inhibitor 1, phosphatase and tensin homologue and cyclin-dependent kinase inhibitor 1 as functional targets of miR-17-5p in multiple conditions [10][11][12]. In this study, as indicated by luciferase reporter assay, we identified TLR4 as a target of miR-17-5p, which is also consistent with a previous report [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To further elucidate the ceRNA network, considering that functional miRNA is known to regulate its target gene expression, the potential target of miR-17-5p was explored by bioinformatics analysis. Previous studies have revealed transforming growth factor-β receptor 2, SRC kinase signaling inhibitor 1, phosphatase and tensin homologue and cyclin-dependent kinase inhibitor 1 as functional targets of miR-17-5p in multiple conditions [10][11][12]. In this study, as indicated by luciferase reporter assay, we identified TLR4 as a target of miR-17-5p, which is also consistent with a previous report [17].…”
Section: Discussionsupporting
confidence: 92%
“…miRNAs also serve as regulator of inflammatory response and have essential roles in diagnosis and treatment of sepsis [9]. miR-17-5p has been shown to have an impact on the outcome of various disorders [10][11][12]. More particularly, miR-17-5p has been suggested as an inflammation-related miRNA and might be associated with sepsis-induced acute lung injury [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA supplementary therapy has become one promising strategy for the treatment of different types of thyroid cancer [18]. MiR-17-5p, as an attractive miRNA, has been reported to serve as an important oncogene in human cancers, such as osteosarcoma, cervical cancer, nasopharyngeal, breast cancer, pancreatic cancer and gastric cancer [8][9][10][19][20][21]. However, its role in thyroid cancer remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Cai et al provided evidence that miR-17-5p promoted cell proliferation and metastasis via regulating transforming growth factor-β receptor 2 (TGFBR2) in cervical cancer [9]. In addition, miR-17-5p could induce proliferation and epithelial-mesenchymal transition by inhibiting SRC kinase signaling inhibitor 1 in osteosarcoma [10]. Previous study demonstrated that miR-17-5p is highly expressed in thyroid cancer [11].…”
mentioning
confidence: 99%
“…Furthermore, classic EMT markers such as N-cadherin, E-cadherin and Snail were quantified by western blot analysis. Finally, it was proven that SRCIN1 is a direct target of miR-17-5p and silencing of this miRNA could change the expression of EMT markers and arrest cell growth (76). SRCIN1 was found to be downregulated in breast cancer in previous studies (77).…”
Section: Mirna-mediated Src Oncogenic Signaling In Selected Cancer Typesmentioning
confidence: 93%